The Two Mafias - Lupo, Salvatore. author. aut Link
XI, 236 p.
Keywords: A realistic understanding of the mafia must avoid depictions both of a monolithic organization and of localized, isolated groups. Here, renowned historian Salvatore Lupo analyzes the mafia as a network of varied relationships and institutions, the result of a complex cultural and social encounter that was shaped by multiple, diverse environments.